Conceptual Framework for the Strategic Management: A Literature Review—Descriptive. (30th January 2020) - Fuertes, Guillermo; Alfaro, Miguel; Vargas, Manuel; Gutierrez, Sebastian; Ternero, Rodrigo; Sabattin, Jorge
Abstract : The objective of this work is to review the literature of the main concepts that lead to determining the strategic approach, creation of strategies, organizational structures, strategy formulation, and strategic evaluation as a guide for the organizational management, taking into account the effects produced by the different types of strategies on the performance of organizations. In this article, the systemic literature review method was used to synthesize the result of multiple investigations and scientific literature. The process of reading and analysis of the literature was carried out through digital search engines with keywords in areas related to the strategic management. This research reveals the lack of scientific literature containing important theoretical concepts that serve the strategists as a guide in the creation, formulation, and evaluation of strategies. This review contributes to the existing literature by examining the impact of the strategic management on the organizational performance.